Accuracy and validity of ultra-short-term heart rate variability from a free mobile application - Pagaduan, J.; Chen, Y.-S. (Journal of Australian Strength and Conditioning, 2020)
This study aimed to establish the accuracy and validity of ultra-short-term recording of heart rate variability (HRV) from a free mobile application. Eighteen physical education male students underwent simultaneous 5-minute recording from electrocardiogram (ECG) and Pulse Express PRO (PE PRO), a free HRV mobile application. Raw data from 5-minute ECG, 60-second PE PRO (PE PRO60), and 30-second PE PRO (PE PRO30) were extracted to derive the root mean square of successive R-R intervals (RMSSD). RMSSD was then transformed to natural log (lnRMSSD). Accuracy was determined using relative error (%RE). The coefficient of variation expressed as typical error of estimate (TEE) and Pearson`s correlation coefficient (r) with 95 percent confidence interval from regression analysis were used to identify validity. Results showed that PE PRO60 posted lnRMSSD with %RE = - 0.57, TEE = 0.20, and r = 0.93 (0.83, 0.97). On the other hand, PE PRO30 lnRMSSD %RE = -0.82, TEE = 0.24, r = 0.89 (0.76, 0.95). The results of the current study support the use of a free mobile application in ultra-short-term HRV recording for practitioners.